A case of dry eye secondary to ocular ischemic syndrome due to carotid artery occlusion. Issue 3 (June 2015) - Perera, Sumith; Ali, Hala; Hoffman, Jeremy; Ceccherini, Andrew
Highlights: Carotid artery occlusion. Ocular ischemic syndrome. Dry eyes. Abstract: A case of unilateral dry eye associated with ipsilateral carotid artery occlusion.